Bridging up challenges and mentality of online learning from pre to post-pandemic to develop ELT performance - Faridah, Eni (JEES (Journal of English Educators Society), 2022)
The transition from face-to-face to digital learning during the pandemic has had a profound impact on students, teachers, parents and policy makers. In practice, the challenges are numerous. Fundamentally, it requires the idea of best practices in the implementation of ELT. The best formulation can be made only when the challenges are comprehensively identified. During 2017-2021, there are several studies examining the challenges of ELT from pre-pandemic to post-pandemic, but only focusing on particular contexts. Thus, this research aims to address those challenges and mentality of e-learning in post-pandemic to develop ELT performance. Whereas the method used in this study is a Systematic Literature Review (SLR) that examines journal articles and proceedings in the 2017-2021 publications according to the topic. The results of this study are a systematic classification of mentality of online learning, ELT challenges, strategy proposed from pre-pandemic to post-pandemic especially in Indonesian context and presented into several subsections; (a) technical challenges, (b) pedagogical challenges, (c) socio-economic challenges, (d) institutional and governmental policies challenges. It is fundamental to identify these challenges in order to come up with the best formula of ELT strategies, such as reconstructing the mentality of learning and integrating roles of various parties. The results of this study provide a comprehensive picture regarding with the reality of ELT during pre-to-post pandemic and as the literature for EFL teachers to develop their professionalism as well as become the considerations for education stakeholders. HIGHLIGHTS : The challenges of teaching English in Indonesia existed prior to the pandemic and worsened during the pandemic despite the fact that there are numerous constructive studies that offer solutions. Many studies have revealed the frequency of challenges in teaching English in Indonesia, including (a) technical challenges, (b) pedagogical challenges, (c) socioeconomic challenges, and (d) institutional and government policy challenges. Several of the identified challenges are fundamentally integrative, which means that one aspect influences the others. As a result, in order to improve the quality of teaching and learning English as a foreign language in Indonesia, all involved parties, including teachers, parents, students, and policymakers, must work together.